Concise medical dictionary - martin , elizbeth a.; Oxford University Press ([Oxford] : Oxford University Press, 1998)
Searchable database of information found in the Concise medical dictionary contains over 10,000 entries. This resource has information from the 2000 corrected reprint of the fifth edition published in 1998.
Title from title screen.
Description based on content as of: March 18, 2002.
Text and search engine.
All Ages.
Also available in print version.
Mode of access: World Wide Web.
Keywords: Medicine -- Dictionaries -- Databases